The Used of English-Indonesian Translation Methods in Hans Christian Anderson’s Short Story “Thumbelina” - Kembaren, Farida Repelita Waty; Afifah, Nabila Yun; Hizbullah, Gilang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study analyzes the translation process used in the Hans Christian Anderson short story